2019
DOI: 10.2147/phmt.s233337
|View full text |Cite
|
Sign up to set email alerts
|

<p>Mothers’ Handwashing Knowledge as a Predictor of Diarrheal Disease Among Under-Five Children Visiting Pediatric Ward in University of Gondar Comprehensive Specialized Hospital, Northwest Ethiopia, 2019</p>

Abstract: BackgroundDiarrheal disease is one of the leading causes of mortality and morbidity among under-five children in the world and often results from contaminated food and water. The aim of this study was to assess the prevalence of diarrheal disease among under-five children visiting the pediatric ward in University of Gondar Comprehensive Specialized Hospital and its association with their mothers’ handwashing knowledge.MethodsAn institutional-based cross-sectional study was conducted from May to July 2019 among… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 25 publications
1
2
0
Order By: Relevance
“…Most recently, in the current RCT of the CHoBI7 mHealth program, 33 diarrhea awareness was a significant mediator of the association between program delivery and observed handwashing with soap and stored drinking water quality at the 12-month follow-up. Furthermore, our finding that awareness of diarrhea prevention was associated with a decrease in diarrhea is consistent with previous studies from Tanzania, Kenya, and Ethiopia, [35][36][37] which showed an association between increased WASH awareness and lower prevalence of diarrheal disease. When responding to IVR messages, participants had to play an active role in demonstrating their knowledge, potentially reinforcing their understanding of diarrhea prevention and highlighting important actions to prevent diarrhea transmission for themselves and their household members.…”
Section: Discussionsupporting
confidence: 92%
“…Most recently, in the current RCT of the CHoBI7 mHealth program, 33 diarrhea awareness was a significant mediator of the association between program delivery and observed handwashing with soap and stored drinking water quality at the 12-month follow-up. Furthermore, our finding that awareness of diarrhea prevention was associated with a decrease in diarrhea is consistent with previous studies from Tanzania, Kenya, and Ethiopia, [35][36][37] which showed an association between increased WASH awareness and lower prevalence of diarrheal disease. When responding to IVR messages, participants had to play an active role in demonstrating their knowledge, potentially reinforcing their understanding of diarrhea prevention and highlighting important actions to prevent diarrhea transmission for themselves and their household members.…”
Section: Discussionsupporting
confidence: 92%
“…Water can be an environmental media for transmitting agents to enter the human body (waterborne disease) and cause infectious disease, both in sanitary water for hygiene purposes such as bathing and washing clothes or drinking water (16)(17). In addition, poor self-hygiene behaviour, such as not washing hands before eating and after defecating, can also be a risk factor for diarrhea (18)(19)(20).…”
Section: Discussionmentioning
confidence: 99%
“…A good hand washing practice was found in 52% of mothers of under five children and the most significant associated factors were knowledge, attitude, and water availability. In another study conducted in Northwest Ethiopia [ 36 ]. Mothers had good handwashing knowledge in 66.05% of instances.…”
Section: Infectious Diseases 1- Hand Washing; 2- Enterovirus; 3- Ostmentioning
confidence: 99%